¿Comer como el discurso médico-nutricional manda? Discursos y prácticas sobre alimentación saludable en sectores medios de la ciudad de Buenos Aires, Argentina. - Flavia Carolina Demonte (Centro Centroamericano de Población, 2021)
Objectives: To describe and analyze the discourses on healthy eating habits and their relationship with declared practices that hold middle-class parents who live in the Autonomous City of Buenos Aires, Argentina. Methods: A qualitative research was conducted, a type of exploratory-descriptive study and data was gathered with semi-structured interviews. Twelve households were intentionally selected, consisting of couples who had children of different age. A thematic analysis strategy was carried out to systematize and analyze the transcriptions. Results: A homogeneous discourse on healthy eating was observed, which is aligned with expert recommendations regardless of the interviewee´s age, whether or not they live with their children, and also their varied food purchasing, preparation, and consumption practices. The diversity observed in these practices can be explained by other criteria which compete with their quest for healthy eating. Even if the benefits of healthy eating to prevent food-related illnesses are recognized, overweight and obesity seem to prevail as the main reasons to choose what to eat, and individual responsibility is articulated. Two are the consequences of the diffusion and incorporation of the medical and nutritional discourse: first, to consider eating practices and body care as issues related to the personal realm; and, second, to leave out the weight that the social context and collective responsibility exert in the explanation of health problems associated with current eating habits.